A prosódia na expressão das atitudes de dúvida, incerteza e incredulidade no português brasileiro - Bruna Ferreira Valenzuela de Oliveira (2011)
The speech does not only transmit the strictly linguistic contents of the sentences but also the speakers expression of attitudes and emotions. In this context, prosody plays an important role, which can result in adding information to the linguistic content and/or its modification. Some measures involving the parameters of frequency, intensity and duration are important prosodic cues in the expression of attitudes in speech. This study aimed to examine how prosodic parameters behave in the expression of doubt, uncertainty and disbelief attitudes. Therefore, we selected 16 performing art students at the end of the course, 8 of each gender living in the city of Belo Horizonte, with age ranging from de 24 to 28 years. Each participant was instructed to utter statements expressing attitudes of doubt, uncertainty and disbelief. The utterance of these statements was made from 30 thoughtful situations, 10 in each attitude, so that the participants felt the need to express the different attitudes. In addition to the attitudes, the participants were also asked to record the reading of the situations, to use as reference for analysis. The data collection and acoustic analysis were performed with the PRAAT®software version 5.1.31. Prosodic parameters were analyzed involving frequency, intensity and duration. Measurements were performed at the statement, projecting the stressed and unstressed vowels. For statistical analysis was used the t test, cluster analysis, logit model, besides assembling the confidence interval for each parameter evaluated. The results revealed that a doubt attitude is characterized by a higher initial fundamental frequency (F0) of the utterance and a lower final F0 in relation to disbelief and uncertainty, maximum F0 and melodic amplitude (MA) of the reduced unstressed vowel, the curve of the tonic vowel F0 isdescending, F0 of utterances peak aligned with the first or second syllable of the utterance, reduced intensity variation, lower duration of the utterance, and stressed and unstressed vowel. The attitude of disbelief was defined by lower pitch range, lower rate of speed melodic variation (RSMV) of the unstressed vowel, F0 minimum aligned with the end of the statement, the greater high intensity and longer duration of the unstressed vowel. The attitude of uncertainty was characterized by higher MA and RSMV of the unstressed vowel, the lower minimum intensity, longer duration of the stressed vowel. It is worth to highlight that theuncertainty was the attitude that showed the greatest number of pauses and prolongations. Thus, it is observed that the attitude of doubt presented itself as the most definite in relation to uncertainty and disbelief. When comparing with the reading, the attitude of doubt shows the greatest number of acoustic parameters manipulated for its expression. Given the above, we conclude that the prosodic aspects had an influence on the expression of each one of the attitudes studied, also contributing to the differentiation between them. Likewise, we realizethat, besides the intonation, parameters of duration and intensity influenced the expression of the attitudes studied.